An Empirical Analysis of Sovereign Credit Risk Co-movement between Japan and ASEAN Countries - Jitmaneeroj, Boonlert; Ogwang, John (Journal of Economics and Behavioral Studies, 2016)
Japan is the most developed economy in Asia. However, it has been on record for being the most heavily indebted country among OECD countries. In many circumstances, the high sovereign debt level indicates a high possibility of sovereign credit risks associated with investment in government bond. The high sovereign credit risk may also generate a number of negative externalities for private businesses operating in the host country. This paper investigates whether sovereign credit risk of Japan as measured by its sovereign credit default swap (SCDS) can better predict and commove with sovereign credit risk of selected ASEAN countries. The bivariate VAR model was used to test for Granger Causalities among these countries SCDS premiums and correlation analysis to investigate co-movements between SCDS of these countries. The results indicate that Japan’s sovereign credit risks do not co-move with those of ASEAN countries, Furthermore, Sovereign credit risks of ASEAN countries tend to lead those of Japan as evidenced by unidirectional causalities from these countries to Japan. The overall suggestion is that sovereign credit risk of Japan is not likely to influence those of ASEAN. The paper concludes with some implications for businesses.